MicroRNA-10b Promotes Nucleus Pulposus Cell Proliferation through RhoC-Akt Pathway by Targeting HOXD10 in Intervetebral Disc Degeneration - Yu, Xin; Li, Zheng; Shen, Jianxiong; Wu, William K. K.; Liang, Jinqian; Weng, Xisheng; Qiu, Guixing (PloS one, 2013)
Aberrant proliferation of nucleus pulposus cell is implicated in the pathogenesis of intervertebral disc degeneration. Recent findings revealed that microRNAs, a class of small noncoding RNAs, could regulate cell proliferation in many pathological conditions. Here, we showed that miR-10b was dramatically upregulated in degenerative nucleus pulposus tissues when compared with nucleus pulposus tissues isolated from patients with idiopathic scoliosis. Moreover, miR-10b levels were associated with disc degeneration grade and downregulation of HOXD10. In cultured nucleus pulposus cells, miR-10b overexpression stimulated cell proliferation with concomitant translational inhibition of HOXD10 whereas restored expression of HOXD10 reversed the mitogenic effect of miR-10b. MiR-10b-mediated downregulation of HOXD10 led to increased RhoC expression and Akt phosphorylation. Either knockdown of RhoC or inhibition of Akt abolished the effect of miR-10b on nucleus pulposus cell proliferation. Taken together, aberrant miR-10b upregulation in intervertebral disc degeneration could contribute to abnormal nucleus pulposus cell proliferation through derepressing the RhoC-Akt pathway by targeting HOXD10. Our study also underscores the potential of miR-10b and the RhoC-Akt pathway as novel therapeutic targets in intervertebral disc degeneration.